Combinatory Actions During Object Play in Psittaciformes (Diopsittaca nobilis, Pionites melanocephala, Cacatua goffini) and Corvids (Corvus corax, C. monedula, C. moneduloides). - Auersperg, Alice M. I.; van Horik, Jayden O.; Bugnyar, Thomas; Kacelnik, Alex; Emery, Nathan J.; von Bayern, Auguste M. P. (Journal of Comparative Psychology, 2015)
The playful (i.e., not overtly functional) combination of objects is considered a potential ontogenetic and phylogenetic precursor of technical problem solving abilities, as it may lead to affordance learning and honing of mechanical skills. We compared such activities in 6 avian species: 3 psittaciforms (black-headed caiques, red-shouldered macaws, and Goffin cockatoos) and 3 corvids (New Caledonian crows, ravens, and jackdaws). Differences in the type and frequency of object combinations were consistent with species' ecology. Object caching was found predominately in common ravens, which frequently cache food. The most intrinsically structured object combinations were found in New Caledonian crows and Goffin cockatoos, which both stand out for their problem solving abilities in physical tasks. Object insertions prevailed in New Caledonian crows that naturally extract food using tools. Our results support the idea that playful manipulations of inedible objects are linked to physical cognition and problem-solving abilities.